IMPLEMENTASI PEMBELAJARAN BERBASIS MASALAH PADA MATA PELAJARAN PKn DALAM MENINGKATKAN KREATIVITAS PESERTA DIDIK DI SMAN 3 PROBOLINGGO - Abdul Basit; Sapriya Sapriya (Jurnal Ilmiah Mimbar Demokrasi, 2016)
ABSTRACT This research is purposed by to describe the efforts of schools in improving the creativity of learners in the subject of Civics through the implementation of PBL. The research methodology used in this research is a qualitative approach with descriptive methods. The research subjects are including principals, teachers, and learners. In collecting the data, the techniques used observation, interviews, and documentation. Data were analyzed using data reduction, data presentation and conclusion/verification. The result of this research shows that the efforts of the school and the principal's role in enhancing the creativity of learners are maximal. It can be proved in the provision of opportunities for learners to explore and to develop the potential and capabilities they had. Schools also provide programs "foster friends" with the purpose diminishes the administrative burden of students, especially those from poor families. Keywords: Problem based learning, civic education, and creativity